Factors affecting luteinizing hormone releasing hormone and somatostatin release from rat hypothalami in virto - Goddard, Elizabeth Anne (Department of Pathology, 2020)
Conditions for the viable maintenance of the isolated rat hypothalamus in culture , have been investigated. Hank's and Earle's media were suitable for incubation but tissue necrosis occurred rapidly in Eagle 's Minimal Essential medium. Hypothalami were suspended in Hank's physiological buffer and factors affecting the release of luteinizing hormone releasing hormone (LHRH) and immunoreactive somatostatin (IRS), investigated. The viability of the tissue was assessed by oxygen consumption and by the rate of protein synthesis. Protein synthesis continued for up to 60 min but declined rapidly during the next 60 min of incubation. Amino acid uptake, however, remained active for 90 min. The rate of LHRH release was constant for the first 60 min of incubation (140 pg/h), thereafter increasing to very high levels (250 pg/h,) concomitant with the decline in protein synthesis, suggestive of loss of cellular integrity and peptide leakage. Release of LHRH from the incubated hypothalamus was found to be a temperature dependent process.